UPAYA CORAL TRIANGLE INITIATIVES (CTI) DALAM MEMBANTU MENGATASI PERMASALAHAN TERUMBU KARANG DI FILIPINA TAHUN 2008-2012 - Dianingrum, Ni Luh Putu Ariesta; Priadarsini, Ni Wayan Rainy; Parameswari, Anak Agung Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2019), 2019)
ABSTRACT   Environmental issues have become the main international agenda. The high threat that occurs due to pressure on marine resources such as unlimited capture of marine products, destructive fishing techniques, land pollution, and climate change increases the risk of damage to the marine and coral reef environment. The purpose of this study was to provide a description of the efforts made by the six Coral Triangle Initiatives (CTI) member countries namely the Philippines, Indonesia, Malaysia, Papua New Guinea, Timor Leste and the Solomon Islands to help overcome coral reef problems in the Philippines. These six countries located in the Coral Triangle region jointly compiled the Regional Plans of Action, which was then followed by the preparation of CTI National Plans of Action by each country. This research is a qualitative descriptive study using library studies in collecting the data. The results showed that the success of the efforts of the six countries established through regionall cooperation can be seen in the preservation of Ang Pulo National Park in the Philippines which has improved the function of its mangrove forests and improved coral reef conditions on Culion Island after improvements to the economic welfare of its people.   Keywords: Coral Triangle Initiatives, Regional Cooperation, Environmental Security,Philippines